Model of Seismic Wave Field Excited by Horizontally Distributed Charge - Xu Qian; Wang Zhong-Qi (Shock and Vibration)
The amplitude-frequency characteristics of seismic wave field excited by an explosive source can directly affect the accuracy of seismic prospecting. To reveal the laws by which the horizontally distributed charge excites the amplitude-frequency characteristics, a method to calculate seismic wave field excited by horizontally distributed charge was studied in this paper. By taking the spherical cavity source model as the basis, the superposition method was applied to obtain the approach of calculating seismic wave field excited by horizontally distributed charge. Compared with numerical simulation, the error of this method was controlled under 7%. As a matter of fact, the distributive charge can effectively reduce the impact on ground vibration and increase the downward seismic wave energy. The charges that are horizontally distributed with 1 m interval can enhance the seismic wave resolution excited by explosive source. The research shows that the established theoretical model can correctly describe the amplitude-frequency characteristics of the seismic wave field excited by horizontally distributed charges.